(untitled) - Wilson, T. Hugh (Dubuque, 2007)
This twenty-first edition of ANNUAL EDITIONS: DRUGS, SOCIETY AND BEHAVIOR provides convenient, inexpensive access to current articles selected from the best of the public press. Organizational features include: an annotated listing of selected World Wide Web sites; an annotated table of contents; a topic guide; a general introduction; brief overviews for each section; a topical index; and an instructor’s resource guide with testing materials. USING ANNUAL EDITIONS IN THE CLASSROOM is offered as a practical guide for instructors.
Keywords: Sử dụng sai thuốc,Drug abuse,Drug abuse,Sử dụng sai thuốc; Phép điều trị,Popular works,Treatment,Công việc phổ biến